Effect of Using Power Air Screw And Cyclone On Air – Fuel Equivalence Ratio And Monoxide Carbon Gas Emissions In Four Stroke Gasoline Engines - Syamsul Arifin (Tibuana, 2021)
The experience is observed for fourstrokes petrol engine for revolution 1000 rpm - 4000 rpm, with used of power air screw oncarburator and cyclone on outlet intakemanifold. Air – fuel mixture have passed ofcyclone to combustion chamber to becometurbulent flow and homogen. Then theexperience of step by step used power screwand cyclone. The first investigation on standarcondition, the second put of power air screwon carburator, the third put of cyclone on outletintake manifold, the fourth put of combinationof power air screw and cyclone. It wasobserving for increasing air – fuel equivalenceratio and reduction of exhaust COconcentration. Actually, used combination ofpower air screw and cyclone are resulted ofcarbon monoxide concentration drop ofenough significant for 2500 rpm and 4000 rpm,respectively 51% and 67%. The carbonmonoxide least concentration is 1,14% oncondition 4000 rpm.